Improving Student Protesters’ Self-Control Through Points of You Coaching - Perdana Kusuma; Tri Sulastri; Dibyo Restu Nugraha; Dwi Yan Nugraha (Al-Qalb : Jurnal Psikologi Islam, 2026)
Student demonstrations in Indonesia are often marked by impulsive behaviors that may escalate into aggressive actions. Self-control plays an important regulatory role in helping individuals manage emotions, impulses, and responses in high-pressure collective settings such as protests. This study examines the effectiveness of Points of You–based coaching in enhancing self-control among university students involved in demonstrations in Makassar. An experimental one-group pretest–posttest design was employed, with self-control assessed using the Brief Self-Control Scale (BSCS) and the Self-Control and Self-Management Scale (SCMS). Data analysis was conducted using R version 4.5.0 in combination with Positron and JASP version 0.95.4.0. Bayesian paired-sample t-tests and Bayesian Linear Regression with a Dichotomous Predictor were used to evaluate changes following the intervention. The results indicate that Points of You coaching effectively improves participants’ self-control, as reflected in increased postintervention scores across both measurement instruments. The practical implications highlight that visual–narrative coaching approaches can serve as a relevant psychological intervention to help students regulate impulsive tendencies during demonstrations, while also supporting educational institutions in promoting more constructive, reflective, and self-regulated forms of collective action.